Actual problems of state regulation of social infrastructure - Mukhamediyeva, G.M. (BUKETOV BUSINESS REVIEW, 2017)
The article explores the basics of the development of social infrastructure in the structure of the social and economic system and social sphere of the state. The author grouped the main directions of state regulation of social infrastructure: regulatory and legal support, program-target regulation, financial regulation and publicprivate partnership. Legal support of minimum social guarantees in modern conditions is shown. Industries are defined that establish and apply minimum social standards in the Republic of Kazakhstan. The most significant factors affecting the program-targeted development of the social infrastructure have been identified. The author analyzed current state programs that establish clear state priorities in the social infrastructure. The author analyzed the state and problems of the development of social infrastructure in the context of industries, identified trends and peculiarities of their changes. The article examines a set of financial methods of state regulation affecting social processes in the country. The author reveals the theoretical and methodological and methodological and practical foundations of the application of public-private partnership in the development of the country's social infrastructure. The article notes that public-private partnership is applicable in the sectors of housing and communal services, education and health. The author suggests ways of improving the development of social infrastructure, taking into account the best practices of regulatory and legal support, program-purpose, financial regulation and public-private partnership.